Thermographic study of the pathological manifestations due to humidity and of the conservation state of the Santa Maria Basilica’s roof - Bru, David; Ivorra, Salvador (Revista ALCONPAT, 2022)
This paper analyzes the current state of the roof of the Basilica of Santa Maria, Alicante, Spain. This building dates back to the 13th century and is catalogued. For the analysis of the efflorescence observed, an analysis of the constructive typology is carried out, as well as a visual analysis of the state of the same, describing the existing pathological manifestations, both in the exterior area of the roofs, as well as in the interior area of the rooms under them. For the technical analysis of the possible leaks from the roof to the interior rooms of the basilica, a watertightness test and the verification through the control of the variation of temperatures by means of thermographic analysis are carried out. It can be concluded the existence and position of leaks that have damaged this listed building.